Determining effective communication strategies for Kansas wheat producers to improve willingness to pay for services - Boswell, Marsha (Kansas State University, 2008)
The Kansas Wheat Commission and the Kansas Association of Wheat Growers offer a number of services to Kansas wheat producers. Kansas wheat producers will be willing to pay more if they perceive they are getting more value from the Kansas wheat organizations. However, Kansas wheat producers are unaware of what the Kansas wheat organizations are doing on their behalf. It is believed that if Kansas wheat producers were more aware of what their organizations were doing on their behalf, they would be willing to contribute more. The overall objective is to improve Kansas wheat producer knowledge of Kansas Wheat activities. A survey of Kansas wheat producers provided data about willingness to pay, importance of services, channel preferences and producer demographics. Funds provided by the Kansas wheat assessment are used for a number of projects and programs. Current programs can be categorized into four areas: research; education, communications, and meetings supporting Kansas wheat growers; domestic market development; and international market development. When asked to rank those four areas from highest to lowest priority, respondents overwhelmingly chose research as the highest priority investment of the Kansas wheat assessment. The survey results indicated that Kansas wheat producers were willing to pay an amount above the current level of 10 mills per bushel for the Kansas wheat assessment. The mean response was 12.42 mills. Members of the Kansas Association of Wheat Growers were willing to pay more for the assessment (15.13 mills per bushel) than non-members. In general, radio is the preferred channel of Kansas wheat producers; however, the two most listed publications and radio stations they rely on for information about wheat were High Plains Journal (33%) and Kansas Farmer (30%), both industry publications. Other producer demographics such as location in the state, type of producer, and acreage also affect producers' willingness to pay.
Keywords: Communication Channels; Agriculture; Kansas Wheat; Willingness-to-Pay; Business Administration, Marketing (0338); Economics, Agricultural (0503); Mass Communications (0708)